Original paperKnowledge of chronic total occlusion among Polish interventional cardiologists - L. Bryniarski, Krzysztof; Zabojszcz, Michał; Dębski, Grzegorz; Marchewka, Jakub; Legutko, Jacek; Surowiec, Sławomir; Siudak, Zbigniew; Żmudka, Krzysztof; Dudek, Dariusz; Bryniarski, Leszek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: Chronic total occlusion (CTO) recanalization is indicated in patients with symptoms and evidence of ischemia, but in most cases those types of lesions are still treated medically. In the last few years CTO angioplasty technique has changed dramatically due to considerable advances in techniques and dedicated equipment. Aim: An attempt to assess the state of knowledge of technical aspects of CTO angioplasty of coronary arteries among Polish interventional cardiologists. Material and methods: Questionnaire survey performed during two major Polish invasive cardiology workshops. Results: In the study there participated 113 physicians with an average length of work experience of 13 years, most of them cardiologists certified as independent primary operators. The majority of respondents recognized the need of prevention of thrombotic complications through control of activated coagulation time during the CTO procedures. Prevention of renal complications and X-ray protection are also recognized as a significant part of the procedures. The benefits from the use of over-the-wire microcatheters and balloons, the proper choice of dedicated guidewires, contralateral injections and retrograde technique are underestimated. Conclusions: Despite satisfactory knowledge about indications and qualification for the CTO procedure, the awareness of procedural aspects (particularly the retrograde technique) as well as the dedicated CTO equipment among Polish interventional cardiologists is still insufficient.